Islamic Education Ideas from KH Saifuddin Zuhri's Perspective - Moni Kusuma Wardani; Zaenal Muttaqin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
KH Saifuddin Zuhri is a student, who diligently studies. KH Saifuddin Zuhri's perspective on Islamic education proves that Islamic education really contributes to Indonesia. For KH Saifuddin Zuhri, the education process is not only at school but starts from the family as the smallest unit. He also revealed that in the education process you must pay attention to the physical health of students until the child's time to play. Until he failed to equalize IAIN when he served as Minister of Religion.